Neutronic Properties Optimization Of The Irt-T Reactor Core - Naymushin A. G. Artem Georgievich; Chertkov Yu. B. Yuri Borisovich; Anikin M. N. Mikhail Nikolaevich; Boyko (Boiko) V. I. Vladimir Ilyich (2016, 2016)
Title screen